Subsurface damage analysis by TEM and 3D FIB crack mapping in alumina and alumina/5vol.%SiC nanocomposites - Wu, H; Roberts, S; Mobus, G; Inkson, B (2003)
TEM and 3D crack analysis by focused ion beam (FIB) cross sectioning have been used to quantify the subsurface damage beneath scratches made by a 120° cone indenter loaded to 1 N in monolithic polycrystalline alumina and alumina/5vol.%SiC nanocomposites. In the nanocomposite, an extensive plastic deformation zone was found under the scratch grooves, extending beyond the first layer of grains to a maximum plastic deformation depth of ∼7 μm below the surface of the track. In the alumina, however, the plastically deformed region only extends to a maximum depth of ∼4 μm and is contained within the first layer of grains adjacent to the groove surface. The 3D morphologies of the cracks under the scratches have been determined by FIB sectioning, showing that a high density of microcracks exists under the scratches in both ceramics. Differences between the plastic deformation and subsurface facture modes of the alumina and the nanocomposite are discussed. © 2002 Acta Materialia Inc. Published by Elsevier Science Ltd. All rights reserved.